Dynamic Prediction of Death in Patients With Tuberculous Meningitis Using Time-updated Glasgow Coma Scale and Plasma Sodium Measurements. (5th April 2019) - Thao, Le Thi Phuong; Wolbers, Marcel; Heemskerk, A Dorothee; Thi Hoang Mai, Nguyen; Thi Minh Ha, Dang; Thi Hong Chau, Tran; Hoan Phu, Nguyen; Van Vinh Chau, Nguyen; Caws, Maxine; Huu Lan, Nguyen; Dang Anh Thu, Do; Thuy Thuong Thuong, Nguyen; et al.
Abstract: Background: Pretreatment predictors of death from tuberculous meningitis (TBM) are well established, but whether outcome can be predicted more accurately after the start of treatment by updated clinical variables is unknown. Hence, we developed and validated models that dynamically predict mortality using time-updated Glasgow Coma Scale (GCS) and plasma sodium measurements, together with patient baseline characteristics. Methods: We included 1048 adults from 4 TBM studies conducted in southern Vietnam from 2004 to 2016. We used a landmarking approach to predict death within 120 days after treatment initiation using time-updated data during the first 30 days of treatment. Separate models were built for patients with and without human immunodeficiency virus (HIV) infection. We used the area under the receiver operating characteristic curve (AUC) to evaluate performance of the models at days 10, 20, and 30 of treatment to predict mortality by 60, 90, and 120 days. Our internal validation was corrected for overoptimism using bootstrap. We provide a web-based application that computes mortality risk within 120 days. Results: Higher GCS indicated better prognosis in all patients. In HIV-infected patients, higher plasma sodium was uniformly associated with good prognosis, whereas in HIV-uninfected patients the association was heterogeneous over time. The bias-corrected AUC of the models ranged from 0.82 to 0.92 and 0.81 to 0.85 in HIV-uninfected and HIV-infected individuals, respectively. The models outperformed the previously published baseline models. Conclusions: Time-updated GCS and plasma sodium measurements improved predictions based solely on information obtained at diagnosis. Our models may be used in practice to define those with poor prognosis during treatment. Abstract : We used time-updated Glasgow Coma Scale and plasma sodium measurements, together with baseline patient characteristics, in a model to dynamically predict death in adults with tuberculous meningitis. Predictions can be made from any time point until day 30 of follow-up.